Effectiveness of distance-based suicide interventions: multi-level meta-analysis and systematic review. Issue 4 (21st July 2022) - Schmeckenbecher, Jim; Rattner, Katrin; Cramer, Robert J.; Plener, Paul L.; Baran, Anna; Kapusta, Nestor D.
Abstract : Background: The use of distance-based interventions (DBIs) to reduce suicidal ideation and behaviours are an increasingly relevant form of intervention. DBIs are more affordable, scalable and available than traditional face-to-face interventions, helping to narrow the gap between needed and provided care. Aims: To evaluate the overall effectiveness of DBIs against suicidal ideation and behaviours. Method: We systematically searched Web of Science, Scopus and PubMed for all DBIs primarily aimed at reducing suicidal ideation and behaviours. Data were analysed with a robust variance estimation corrected, multi-level meta-analysis. Results: We found 38 studies, reporting 110 outcomes. Effectiveness in reducing suicidal ideation was low (standardised mean difference −0.174, 95% CI −0.238 to −0.110). DBIs were significantly less effective against suicidal behaviours than against suicidal ideation, although still effective (standardised mean difference −0.059, 95% CI −0.087 to −0.032). Human involvement had no significant effect on effectiveness. Conclusions: Despite low effectiveness, DBIs might play a role in large-scale prevention efforts against suicidal ideation within a stepped care approach. Further, DBIs may be helpful in expanding mental health services in low- and middle-income countries with otherwise limited access to mental healthcare. Although the evidence for DBIs efficacy is well grounded, the technical and scientific evaluation of DBIs regarding their set up, functionality and components needs to be addressed in future studies.